2021
DOI: 10.1109/access.2021.3115425
|View full text |Cite
|
Sign up to set email alerts
|

ProLab: A Perceptually Uniform Projective Color Coordinate System

Abstract: The work was partially financially supported by RFBR in the context of scientific projects N o N o 17-29-03370 and 19-29-09075.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We find such an approach to be optimal for proLab as well as for CIELAB, since for both systems the inaccuracy in uniformity is too significant to be fixed by a separate optimization. That is why for light sources other than D65, we suggest using the same elements of the matrix Q as in (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find such an approach to be optimal for proLab as well as for CIELAB, since for both systems the inaccuracy in uniformity is too significant to be fixed by a separate optimization. That is why for light sources other than D65, we suggest using the same elements of the matrix Q as in (44).…”
Section: Discussionmentioning
confidence: 99%
“…• The transformation from CIE XYZ to proLab has an elegant analytical expression, and it is computationally efficient compared with CAM16-UCS and the even more primitive CIELAB. We presented the idea of constructing the proLab coordinate system for the first time at 25th Symposium of the International Society for Color Vision in 2019 [44], but the construction methodology and a numerical study of proLab properties in detail are discussed for the first time in the current work . Moreover, the model parameters have been estimated more accurately compared to the one presented at the Symposium.…”
Section: G Proposed Colour Coordinate Systemmentioning
confidence: 99%
“…After a period of pressurisation, it is found that the luminescence phenomenon first occurs near the electrode, and it is a distinct green light as shown in Figure 3g. The Commission Internationale de L'Eclairage (CIE) coordinate (X, Y) is used to quantitatively represent the luminescent colours [38,39], where X represents the red component and Y represents the green component. As shown in Figure 3h, all the monochromatic light lies on the tongue curve, and the specific location of the colour light emitted by the sample is marked as (0.2413, 0.5915), which is within the range of green light.…”
Section: Microstructure and Luminescence Analysismentioning
confidence: 99%
“…The spatial filtering method employed in S-CIELAB can be also utilized in different color coordinates and color difference metrics, such as those proposed in [28,29]. Furthermore, another model, N-CIELAB [30], can be used to simulate the properties of the contrast sensitivity of the human visual system.…”
Section: Similarity Assessment Between the Two Imagesmentioning
confidence: 99%